A comunicação do enfermeiro na Estratégia Saúde da Família - Antunes, Josiane Fernandes Gomes (2018)
Overall objective: To analyze or nurses communication process with multidisciplinary team of a Family Health Strategy. Materials and Methods: Descriptive study with a qualitative approach. It was developed in Family Health Units of Aracaju and consists of eight nurses who work in the Family Health Strategy of this municipality. For choice of Health Units, random lottery was drawn. The data collection technique used was the focus group, performed during the months of September and October / 2017. To analyze the data, we used content analysis, based on Berlo's theory of communication (2003). Results: It was evidenced that nurse's communication in the Family Health Strategy is permeated by discourses aimed at health professionals, managers and patients. With regard to communication with the multidisciplinary team in health, it is informative and persuasive, mainly performed verbally, through team meetings and little focused on the understanding, relationship and transformation of and organizational space. Final considerations: Although nurse seeks communication based on the understanding and perception of reality, it is verified that there is a need for a more interactive dialogue in order to promote a more participatory space with management and health team members. This is possible through actions that promote management support to the nurse, and greater closeness and dialogue between nurses and health team members.